Design of an instrument to measure alcohol-related psychosocial influences in the development of norms among 13-year-old to 17-year-old adolescents. Issue 8 (19th August 2013) - Hildebrand, Janina; Maycock, Bruce; Burns, Sharyn; Zhao, Yun; Allsop, Steve; Howat, Peter; Lobo, Roanna
Abstract : Introduction: Harmful drinking among young people is common in Australia and many other countries. Social norms and their influence on adolescents' alcohol consumption behaviours have received much research attention in recent years. However, there is limited understanding of how social norms related to alcohol are developed and transmitted across social networks and a specific tool that measures these constructs has yet to be developed. This paper outlines the rationale and protocol for the design and validation of a multidimensional survey instrument which measures the development and transmission pathways of alcohol-related norms among adolescents. A longer term aim is to apply the instrument in a respondent-driven sampling study with a large adolescent cohort. Methods and analysis: Social Cognitive Theory (SCT) and relevant literature will guide the design of the online survey instrument. Feedback from a practitioner-based stakeholder committee, academic expert panel reviews, focus groups and interviews with adolescents aged 13–17 years in Perth, Western Australia (WA) will serve to ascertain content and face validity. A test–retest will be conducted using a purposive sample of students (n=400) at secondary schools in Perth. The instrument's psychometric properties will be analysed, including exploratory factor analyses, discriminant validity, internal consistency and test–retest reliability. Ethics and dissemination: The results of this research will provide public health researchers and practitioners with a comprehensive standardised instrument to explore the characteristics of individual-level and community-level social influences and norms associated with use of alcohol by adolescents and the routes through which these norms are transmitted. The data collected by the instrument is anticipated to inform the design of youth specific interventions with the potential to reduce alcohol-related harms. The Study findings will be disseminated widely through peer-reviewed publications and conference presentations. The study has received approval from the Curtin University Human Research Ethics Committee.